New developments in combating infection from biofilm forming bacteria of orthopedic implants - Sharma, Pulkit; Ayaz, Saqib; Gupta, Sanjeev; Singh , Rahul (International Journal of Research in Orthopaedics, 2023)
Orthopedic device related infections (ODRI’s) represent a difficult to treat situation owing to their biofilm based nature. Biofilm infections once established are difficult to eradicate even with an aggressive treatment regimen due to their recalcitrance towards antibiotics and immune attack. The definitive treatment to eradicate the infections once a biofilm has established is surgical excision of the implant and thorough local debridement, but this carries a significant socioeconomic cost, the outcomes for the patient are often poor, and there is a significant risk of recurrence. The aim of the study was to provide a comprehensive insight into the newer anti-biofilm interventions (non-antibiotic approaches) and a better understanding of their mechanism of action essential for improved management of orthopedic implant infections.